2009
DOI: 10.1177/147323000903700338
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Procalcitonin in Gynaecological Surgery

Abstract: We evaluated postoperative concentrations of inflammatory indicators, including procalcitonin, after gynaecological operations for benign and malignant tumours in patients with a normal postoperative course and assessed the utility of procalcitonin in differentiating between non-bacterial inflammation and bacteraemic complications in the postoperative period. This prospective study included 99 patients: 47 after a standard gynaecological operation (Piver I) and no postoperative infectious complications (group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…30 Increased PCT concentrations in the terminal phase of a malignancy are discussed as a result of local release of inflammatory mediators from the necrotizing tumour. 31 In addition to bacterial toxins, some cytokines like tumour necrosis factor (TNF)-a and IL-6 are able to trigger PCT synthesis. 31 It has to be emphasized that some of the cancer patients might have suffered from a concomitant infection, for example, pneumonia, urological tract infection, resulting in elevated markers of inflammation.…”
Section: Nop -Pn/ofq and Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…30 Increased PCT concentrations in the terminal phase of a malignancy are discussed as a result of local release of inflammatory mediators from the necrotizing tumour. 31 In addition to bacterial toxins, some cytokines like tumour necrosis factor (TNF)-a and IL-6 are able to trigger PCT synthesis. 31 It has to be emphasized that some of the cancer patients might have suffered from a concomitant infection, for example, pneumonia, urological tract infection, resulting in elevated markers of inflammation.…”
Section: Nop -Pn/ofq and Inflammationmentioning
confidence: 99%
“…31 In addition to bacterial toxins, some cytokines like tumour necrosis factor (TNF)-a and IL-6 are able to trigger PCT synthesis. 31 It has to be emphasized that some of the cancer patients might have suffered from a concomitant infection, for example, pneumonia, urological tract infection, resulting in elevated markers of inflammation. However, only one patient was diagnosed with infection.…”
Section: Nop -Pn/ofq and Inflammationmentioning
confidence: 99%
“…Similar to CRP, few studies highlighted the role of procalcitonin in advanced gynaecological malignancies [119], one of which was a study on ovarian cancer [120]. We discovered that the median value of procalcitonin was more remarkable in advanced-stage VC than in the early stage (0.67 vs. 0.05, p = 0.044).…”
Section: Discussionmentioning
confidence: 76%
“…PCT is one of the most important variables that enables us to distinguish infection-induced inflammation from non-infection-induced inflammation [26], and it has become widely used as a biomarker for bacterial infection as well as a role in highlighting the effectiveness of antibiotic therapy, in addition to its widespread adoption in intensive care units to monitor and control the severity of sepsis [27]. Several studies have demonstrated that PCT also plays a role in predicting postoperative complications for a variety of operations such as colorectal, cardiac, and gynecological surgeries [17,28,29]. However, due to a lack of studies that have investigated PCT, its importance in pancreatic surgery and in predicting its complications has remained understudied.…”
Section: Original Articlementioning
confidence: 99%